Impact of High BMI on Wound Complications in Open Paraumbilical Hernia Repair - Hassan Shahab, Omer Bin Khalid, Bushra Jawaid, Sumbla Salman, Unaiza Erum, Komal Faheem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background/Objective: Few studies have clearly shown a correlation between obesity and wound complications. We analyzed the correlation between body mass index and the complication rate of mesh-based open paraumbilical hernia repair. Method: This observational study after the approval from the institute review board using non-probability consecutive sampling, recruited 150 participants scheduled to have open mesh surgery for paraumbilical hernia repair from 01/may/2022 to 30/Oct/2022 at Department of General Surgery, Civil Hospital Ruth Pfau, DUHS, Karachi and divided into two groups; BMI 26-30 (n=62) and BMI 31-36 (n=88). Completed surveys were analyzed for demographic and clinical data, hernia features, surgical procedures, and patient outcomes. Results: The average age of the participants in the present study was 44.32 years, with an average BMI of 30.97 kg/m2. Out of 150 recruited participants 78 were female and 72 were males. Mean hernia width of the recruited participants was 10.12, with average operative time of the participants was 101.58 minutes. The Mean± S.D of hospital stay (days) of both study groups was 0.82±0.61 and 2.55±0.77 years, and a significant association (0.000) in their mean difference was observed. 26% participants in BMI (26-30) and 58% participants in BMI (26-30), got readmitted to hospital and a significant association (0.000) in their mean difference was observed. 13% participants in BMI (26-30) and 43% participants in BMI (26-30), got wound infection and a significant association (0.000) in their mean difference was observed. Practical implication: this study will help to understand what type of surgery procedures can be beneficial in different BMI classes. Conclusion: The developing SSI and SSOPI after paraumbilical hernia repair rise steadily with increasing BMI. More research is needed to see whether dropping some pounds before surgery will mitigate this correlation. Keywords: paraumbilical hernia repair, BMI, Wound infections, Wound classification.